2016
DOI: 10.1177/0013161x16648190
|View full text |Cite
|
Sign up to set email alerts
|

Equitable Access for Secondary English Learner Students

Abstract: Purpose EL education policy has long directed schools to address English learner (EL) students’ linguistic and academic development, and must do so without furthering inequity or segregation (Lau, 1974; Castañeda, 1981). The recent ESSA (2015) reauthorization expresses a renewed focus on evidence of equity, effectiveness, and opportunity to learn. We propose that high school course taking patterns provide evidence of program effectiveness and equity in access. Research Design Using data from the nationally r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(40 citation statements)
references
References 60 publications
0
40
0
Order By: Relevance
“…2 Crowding out is also indicative of exclusionary tracking as emergent bilinguals within DLBE are clustered and thereby furnished with a similar master schedule (Umansky, 2016). Although DLBE students are not as highly represented in remedial courses relative to their peers in ESL program models, their schedule is still mostly basic, yielding fewer opportunities for advanced placement in middle school and affecting future advanced-level high school courses (Callahan, 2005;Callahan & Shifrer, 2016).…”
Section: Electives and Crowding Outmentioning
confidence: 99%
“…2 Crowding out is also indicative of exclusionary tracking as emergent bilinguals within DLBE are clustered and thereby furnished with a similar master schedule (Umansky, 2016). Although DLBE students are not as highly represented in remedial courses relative to their peers in ESL program models, their schedule is still mostly basic, yielding fewer opportunities for advanced placement in middle school and affecting future advanced-level high school courses (Callahan, 2005;Callahan & Shifrer, 2016).…”
Section: Electives and Crowding Outmentioning
confidence: 99%
“…As such, newcomers were denied access to grade level curriculum and content, a violation of U.S. Department of Education's recommendations for servicing ELs' language and content needs (USDOE, 2017). The impact of inequitable access was studied by Callahan and Shifrer (2016), who found that ELs language status significantly impacted their access to academic rigor and exposure in educational programs. The lack of exposure led to sustained achievement gaps between ELs and their non-EL peers.…”
Section: Theme One: Institutional Barriers and The Development Of Capmentioning
confidence: 99%
“…The curriculum ultimately demonstrates how opportunities to learn can be cultivated for ELs as well as other language learners in a wide range of academic contexts. area curricula has high-stakes implications for ELs in secondary grades; subpar curricula deprive ELs of the opportunity to learn, thus poorly positioning them for postsecondary education (Kanno & Kangas, 2014;Callahan & Shifrer, 2016;Kanno, 2018).…”
Section: Lehigh Universitymentioning
confidence: 99%
“…With principles of L2 learning embedded naturally throughout tasks, geospatial learning holds great promise for ELs in secondary grades. The confluence of L2 and academic learning cannot be overvalued, because ELs frequently encounter either inadequate L2 support or watered-down content learning (Callahan & Shifrer, 2016;Umansky, 2016a;Valdés, 2001). The U.S.…”
Section: Implications and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation